Effect of tidal submergence on potassium nutrition and yield of rice (Oryza sativa L.) - Haque, MA (Bangladesh Journal of Agricultural Research, 2012)
Field experiments were conducted at Patuakhali Science and Technology University research farm during 2009 T. Aman season to investigate the effect of tidal submergence on potassium nutrition and yield of rice. The experiment included two levels of irrigation water source- i) tidal water and ii) ground water, and three levels of fertilizers- i) absolute control (no fertilizer), ii) NP (K omission), and iii) NPK (K addition). The rice varieties were BR23 (HYV) and Lalmota (traditional variety). A general increase in growth, yield and yield contributing parameters were found due to irrigation with tidal water. Tidal water contributed about 19% (BR23) and 11% (Lalmota) higher grain yield in Aman season 2009 compared to that grown with ground water. Potassium contents of rice grain and straw were always higher when plants are irrigated with tidal water. In general, tidal submergence increased K uptake of rice. The K uptake by BR23 under tidal water was about 47, 43 and 8 kg/ha more than those recorded with ground water irrigation under absolute control, K omission and K addition treatments, respectively whereas it was 31, 21, and 68 kg/ha, in Lalmota. The results indicated that whether fertilizers were applied or not plants absorb considerable amount of K from tidal water. Bangladesh J. Agril. Res. 37(3): 433-439, September 2012 DOI: http://dx.doi.org/10.3329/bjar.v37i3.12086